Genetic Variability, Correlation and Path Analysis in Stem Amaranth (Amaranthus tricolor L.) Genotypes (The Agriculturists, 2013)
Seventeen genotypes of stem amaranth (Amaranthus tricolor L.) were evaluated to determine the genetic variability, degree of association between yield and its component characters. The direct and indirect effects of marketable yield were also evaluated. High heritability with high genetic advance as percent of mean was registered for number of leaf, leaf weight and marketable yield which in fact demonstrated the presence of additive gene effects. The correlation studies revealed strong positive association of yield with leaf weight, stem weight, stem diameter, dry weight with rind, and dry weight without rind. The relationship was non-significant and negative at 1st flowering. The result of path analysis indicated that stem weight had maximum direct effect on marketable yield followed by leaf weight, leaf number and dry weight without rind. DOI: http://dx.doi.org/10.3329/agric.v11i1.15235 The Agriculturists 2013; 11(1) 1-7